(untitled) (Bangladesh Medical Journal, 2022)
Vitamin D is essential for the maintenance of calcium and phosphorus homeostasis. It has skeletal growth and extra-skeletal effects in our body. Objective of this article is to update the information on skeletal and extra-skeletal effects of vitamin D deficiency in paediatric clinical disorders. In the paediatric population, vitamin D deficiency is associated with different clinical diseases such as rickets, insulin resistance, metabolic syndrome, respiratory tract infections, asthma, and autoimmune diseases. It is associated with prematurity, obesity, malabsorption, anticonvulsant agents, extreme latitudes, low consumption, and little sun exposure. The recommendation is to prevent vitamin D deficiency and to maintain 25(OH) D serum levels >30ng/mL (>75 nmol/L). Bangladesh Med J. 2021 Sept; 50(3): 36-43